Características biológicas y reproductivas de Engytatus varians (Distant) y Dicyphus maroccanus Wagner (Hemiptera: Miridae), depredadores zoofitófagos de plagas de solanáceas - Mena Mociño, Laura Verónica (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
The influence of three sex ratios (1: 1, 2: 1 and 3: 1 male: female) of Engytatus varians (Distant) (Hemiptera: Miridae) was evaluated on the total number of progeny, fertility and female longevity as well as the duration of nymphal development and sex ratio of offspring. The female sex ratio 3:1 produced more offspring than the other ratios. The fecundity of females was inversely related to increasing age in the three tested proportions. The longevity of females decreased when the number of males is increased. Sex ratio influenced the duration of the nymphal development of the offspring. Sexual proportion parent did not affect the sex ratio of offspring. Engytatus varians predation on different nymphal instars of Bactericera cockerelli was also evaluated in two ways: a) each instar B. cockerelli it was placed in various tomato leaflets; and b) the different instars of B. cockerelli were randomly placed in one leaflet. The two scenarios predation showed that males and females as well as N3, N4 and N5 E. varians nymphs had preference for consuming second instar nymphs of B. cockerelli. In this research, the effect of the type of prey and host plant on biological (fecundity, longevity, the oviposition rate) and demographic parameters (the net reproductive rate, the intrinsic rate of increase, generation time) of Dicyphus maroccanus Wagner (Hemiptera: Miridae) were also evaluated.

La influencia de tres proporciones sexuales (1:1, 2:1 y 3:1; macho:hembra) de Engytatus varians (Distant) (Hemiptera: Miridae) fue evaluada sobre el número total de progenie, fecundidad y longevidad de las hembras, así como en la duración del desarrollo ninfal y proporción sexual de la descendencia. Las hembras de la proporción sexual 3:1 produjeron más descendencia que las otras proporciones. La fecundidad de las hembras fue inversamente proporcional al incremento de la edad en las tres proporciones ensayadas. La longevidad de las hembras disminuyó cuando se incrementó el número de machos. Las proporciones sexuales influyeron en la duración del desarrollo ninfal de los descendientes. La proporción sexual de los progenitores no afectó la proporción sexual de los descendientes. También se evaluó la depredación de E. varians sobre los distintos instares ninfales de Bactericera cockerelli en dos experimentos: a) cada instar de B. cockerelli se colocó en distintos foliolos de una hoja de tomate; y b) los distintos instares de B. cockerelli se colocaron en forma aleatoria en un solo foliolo. Los dos escenarios de depredación mostraron que las hembras y machos, así como las ninfas N3, N4 y N5 de E. varians mostraron preferencia por consumir ninfas de segundo instar de B. cockerelli. En esta investigación también se evaluó el efecto que tiene el tipo de presa y planta hospedera en los parámetros biológicos (fecundidad, longevidad, tasa de oviposición) y demográficos (tasa intrínseca de crecimiento poblacional, tasa de reproducción neta y tiempo generacional) de Dicyphus maroccanus Wagner (Hemiptera: Miridae).
Instituto de Investigaciones Agropecuarias y Forestales. Maestría en Producción Agropecuaria
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2016-0267; Control biológico; Fecundidad; Planta hospedera; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6583